2010
DOI: 10.1007/s10792-010-9382-z
|View full text |Cite
|
Sign up to set email alerts
|

Deep sclerectomy with the Ex-PRESS X-200 implant for the surgical treatment of glaucoma

Abstract: The efficacy and safety of a newly designed Ex-PRESS X-200 drainage device for the surgical treatment of glaucoma was evaluated. A clinical, prospective, monocentric, non-randomised, unmasked study on patients with medically uncontrolled glaucoma was performed. A superficial scleral flap was created. A posterior deep sclerectomy (DS) was dissected without opening the Schlemm's canal and an Ex-PRESS X-200 device was inserted under the scleral flap into the anterior chamber to drain aqueous humour into the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…[ 6 , 9 , 25 , 57 , 59 , 61 ] In contrast with trabeculectomy, Ex-PRESS implantation is less invasive and causes less complications, subsequent inflammation, less IOP variance and faster recovery during the early postoperative period. [ 34 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 54 ] The biomolecular findings of 1 animal study also proved the similar results, which showed lower levels of transforming growth factor β2 after Ex-PRESS implantation under a scleral flap, compared with filtering sclerostomy in rabbits. [ 63 ] In our study, only 1 patient (Patient 4) had postoperative hyphema, and the extent of hyphema was mild enough that it spontaneously resolved in 2 weeks without surgical intervention.…”
Section: Discussionmentioning
confidence: 55%
“…[ 6 , 9 , 25 , 57 , 59 , 61 ] In contrast with trabeculectomy, Ex-PRESS implantation is less invasive and causes less complications, subsequent inflammation, less IOP variance and faster recovery during the early postoperative period. [ 34 39 , 41 , 42 , 44 , 45 , 47 , 48 , 50 54 ] The biomolecular findings of 1 animal study also proved the similar results, which showed lower levels of transforming growth factor β2 after Ex-PRESS implantation under a scleral flap, compared with filtering sclerostomy in rabbits. [ 63 ] In our study, only 1 patient (Patient 4) had postoperative hyphema, and the extent of hyphema was mild enough that it spontaneously resolved in 2 weeks without surgical intervention.…”
Section: Discussionmentioning
confidence: 55%
“…Our longterm outcomes are similar to the previous short-and mid-term results reported earlier. 1,3,4,[8][9][10][11][12][13][16][17][18][19][20][23][24][25] The complete success rate in our study shows a decline from 83% at 1 year to 57% at 5 years. In a similar manner, de Jong et al 20 report on a complete success rate decline from 86.8% at 1 year to 59% at 5 years with the EX-PRESS.…”
Section: Discussionmentioning
confidence: 84%
“…(Bissig et al, 2010) A posterior deep sclerectomy was dissected without opening the Schlemm's canal and an Ex-PRESS X-200 device was inserted under the scleral flap into the anterior chamber to drain aqueous humour into the intrascleral space. Eighty-five percent of patients achieved an IOP < 18 mmHg with or without medication and 69% without medication.…”
Section: Ex-press With Deep Sclerectomymentioning
confidence: 99%